2018
DOI: 10.1051/alr/2018002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of biochemical composition of Noah's ark shells (Arca noaeL. 1758) in a Tunisian coastal lagoon in relation to its reproductive cycle and environmental conditions

Abstract: The seasonal changes in biochemical composition of the edible bivalve Arca noae harvested from a Mediterranean coastal lagoon (Bizerte lagoon, Tunisia) were investigated from October 2013 to September 2014. Potential food sources and nutritional quality indices (NQI) were determined by analyzing the fatty acid profiles of their tissues during an annual reproductive cycle. Results showed that A. noae had moisture (73.8–82%) and protein (24.1–58.6% dry weight) as major components, followed by lipid (10.4–28.8% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
7
0
1
Order By: Relevance
“…In our previous research, we reported that A. noae body dry weight (BDW) is relatively constant during the first reproductive phase (from October to March), while it increased significantly during the second phase from April to reach its maximum in July indicating a rapid increase in biomass caused by growth of gonadal and somatic tissues (see Ghribi et al 2017). This increase coincided with high food uptake (Chl a) in the lagoon waters and important reserve materials accumulation (Ghribi et al 2018). The use of the gonad index (GI), as a descriptor of the ecophysiological and health status of marine organisms, reflected in part the evolution of the sexual cycle of A. noae in the Bizerte lagoon (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous research, we reported that A. noae body dry weight (BDW) is relatively constant during the first reproductive phase (from October to March), while it increased significantly during the second phase from April to reach its maximum in July indicating a rapid increase in biomass caused by growth of gonadal and somatic tissues (see Ghribi et al 2017). This increase coincided with high food uptake (Chl a) in the lagoon waters and important reserve materials accumulation (Ghribi et al 2018). The use of the gonad index (GI), as a descriptor of the ecophysiological and health status of marine organisms, reflected in part the evolution of the sexual cycle of A. noae in the Bizerte lagoon (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the fatty acid composition of V. decussata from the Tunisian Coast presented a prevalence of unsaturated fatty acids (UFA) throughout the study sites. According to many investigations, this higher amount of UFA was specific to a healthy marine species (Ghribi et al, 2018). In fact, the PUFA levels in clam tissues reached their highest values, which coincided with an important amount of Chl a and lower T °C.…”
Section: Discussionmentioning
confidence: 91%
“…In the Mediterranean Sea, mainly in Tunisia, bivalves are considered as a rich food source and a healthy proportionate diet [3,42]. Since, they are known for their nutritious and essential energy reserves (e.g., protein, vitamins and minerals).…”
Section: Discussionmentioning
confidence: 99%